Choline transporter‐like protein 4 (CTL4) links to non‐neuronal acetylcholine synthesis. (25th June 2013) - Song, Pingfang; Rekow, Stephen S.; Singleton, Corey‐Ayne; Sekhon, Harmanjatinder S.; Dissen, Gregory A.; Zhou, Minerva; Campling, Barbara; Lindstrom, Jon; Spindel, Eliot R.
Abstract: Synthesis of acetylcholine (ACh) by non‐neuronal cells is now well established and plays diverse physiologic roles. In neurons, the Na + ‐dependent, high affinity choline transporter (CHT1) is absolutely required for ACh synthesis. In contrast, some non‐neuronal cells synthesize ACh in the absence of CHT1 indicating a fundamental difference in ACh synthesis compared to neurons. The aim of this study was to identify choline transporters, other than CHT1, that play a role in non‐neuronal ACh synthesis. ACh synthesis was studied in lung and colon cancer cell lines focusing on the choline transporter‐like proteins, a five gene family choline‐transporter like protein (CTL)1–5. Supporting a role for CTLs in choline transport in lung cancer cells, choline transport was Na + ‐independent and CTL1–5 were expressed in all cells examined. CTL1, 2, and 5 were expressed at highest levels and knockdown of CTL1, 2, and 5 decreased choline transport in H82 lung cancer cells. Knockdowns of CTL1, 2, 3, and 5 had no effect on ACh synthesis in H82 cells. In contrast, knockdown of CTL4 significantly decreased ACh secretion by both lung and colon cancer cells. Conversely, increasing expression of CTL4 increased ACh secretion. These results indicate that CTL4 mediates ACh synthesis in non‐neuronal cell lines and presents a mechanism to target non‐neuronal ACh synthesis without affecting neuronal ACh synthesis. Abstract : It is now well established that many non‐neuronal cell types synthesize and secrete acetylcholine that acts as an autocrine or paracrine hormone. Although there are many similarities between neuronal and non‐neuronal acetylcholine synthesis, there is a difference in choline transport for acetylcholine synthesis. Neurons must use the high affinity choline transporter CHT1, but many non‐neuronal cells synthesize acetylcholine without CHT1. In this article, we show that non‐neuronal cells utilize the choline transporter‐like protein‐4 (CTL4) for ACh synthesis.